Respuesta :

Answer:

The given  system as (3,3) as its solution.

Step-by-step explanation:

Here, the given system of the equation is:

4 x + 2 y = 18 ................  (1)

2 x + 3 y = 15      ...............  (2)

Now, to use the elimination method, w need to eliminate any of the variable.

Eliminate the variable x in the given system.

Multiply equation (2) with -2  we get,

(2 x + 3 y = 15  )(-2) ⇒ -4x - 6y = -30  .......  (3)

Add (1) and (3), we get:

4 x + 2 y   -4x - 6y    = 18  -30

or, - 4 y = - 12

or, y =  12/4 = 3    ⇒ y = 3

Putting in (1), we get

4x + 2(3)   = 18  or, 4x    = 18 - 6 = 12

or, x  = 3

(x,y)  = (3,3)

Hence, the above system as (3,3) as its solution.